Hysteresis dynamic model of metal rubber based on higher-order nonlinear friction (HNF). (15th April 2023) - Zhou, Chunhui; Ren, Zhiying; Lin, Youxi; Huang, Zihao; Shi, Linwei; Yang, Yu; Mo, Jiliang
Graphical abstract: Highlights: A high-order nonlinear friction (HNF) model was proposed for the first time according to the inclination angle and contact form of the spatial distribution of metal wires in MR. The HNF hysteresis dynamic model was constructed from which the NHF was the influence factor to adapt to the change of process parameters of metal rubber. The probability function of three contact forms was constructed from the estimated parameters. And the transferred probability of three contact forms was analyzed under a harmonic excitation with 10 Hz. Abstract: Metal rubber (MR) is a kind of porous and highly elastic pure metal damping material, but its strong nonlinear hysteresis characteristics are the main factors limiting its engineering application. In this paper, a high-order nonlinear friction (HNF) model was proposed for the first time according to the inclination angle and contact form of the spatial distribution of metal wires in MR. At the same time, combined with nonlinear elastic restoring force, nonlinear damping force, and coulomb hysteresis friction force, a general hysteresis dynamic model of MR was constructed. In order to verify the accuracy of the model, three kinds of MR with different densities were prepared and tested. The results show that the HNF hysteresis dynamic model has a very high prediction accuracy ( R 2 = 0.9999 ) and a high signal-to-noise ratio ( SNR > 700 ). The hysteresis curve of the HNF hysteresis dynamic model was highly consistent with the experimental hysteresis curve, while the accuracy and versatility of the traditional dynamic model decreased with the change of density. It is because the HNF term includes the influence factors that can characterize the contact form of the metal wire inside MR and the material properties. These influence factors will be adjusted in real-time to reduce the error of the model according to the changes in the preparation process parameters or material properties. Therefore, the HNF hysteresis dynamic model could effectively demonstrate the nonlinear hysteresis characteristics of MR and had the adaptive ability to change process parameters. This paper provided a new theoretical model for the dynamic system of MR materials with a complex network structure.